Effort of Between-Countries Border Society in Maintaining Social Welfare - Kuntjorowati, Elly (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research is aimed to describe the border community efforts between countries in West Kalimantan especially in maintaining social welfare. This study has 60 respondents taken out of people from rural communities at Jagoi, Jagoi Babang Sub-District, Bengkayang District, West Kalimantan Province, and supportive informants such as stakeholders and community leaders. This decision was carried out purposively in accordance with the needs of relevant data to this research. The data was collected through in-depth interviews, observation and documentation study on secondary data related to the research topic. The respondents were selected on the base of appropriateness to the research goal criteria. The data captured are analyzed qualitatively and are presented in percentage to gain some information which described the border society efforts in maintaining the social welfare. The results showed that the location of the village of Jagoi, Jagoi Babang Sub- District was very far away from the center of government in neither central nor local government, and it was really difficult to reach the location because it was located in the mountainous area, so that the infra-structure built up there was still very inadequate. Education and health facilities were still very minimal, Human Resources capability was still at very low level, there were a lot of unemployment, index of poverty was very high, so that it was much more difficult to maintain their social welfare, and their economic activities depended much on their neighbor country of Malaysia, which in turn brought an impact on the lack of nationalism because of their expectation in earning more Ringgit rather than Rupiah.